REGIONAL STATES IN SOUTHEAST EUROPE BETWEEN EUROREGIONALISM AND ETHNOREGIONALISM - Izet Ibreljić; Salih Kulenović; Amra Kožarić (European Regional Science Association (ERSA), 2010)
Regional policy of European Union promoted a long time ago uniformly regional development as one of its own integration priority, and each phase in integration process of individual states monitoring appropriately growing distribution of the financial assets, which helps them to accomplish those developing goals. However, in regional Europe are also present disintegrations, which are solving by upgrading already accomplished self-determination of few regions by cultural, political and economical model of government. Therefore, pro-European regionalism architects primary present the citizen as active social subject. In Southeast Europe, with big political and economical diversity, and territorial dispersion of nations, the discussion about different aspects of regionalism are becoming more and more significance. This area is characteristic by cultural diversity, disbelief, political barriers, stereotype, which are crowded by centuries. The escalation of the abduct ethno-nationalistic polities, at the end of the last century, lead here to the wars and "ethnic cleaning". All that, complicate the realization of the euro-regional concept, and also threat further fragmentation of this area and don't conduce to developing mutual identity of this region. Regionalization and balanced regional development are here main criterion for incorporation in European economical structure, but also for democratization and society development. The object of this research is to examine the possibilities of regionalization and balanced regional development of geo-area Southeast Europe, in context existing euro regional standards. To this end, it is necessary, throw complexly analysis of EU experiences in this area, which can be also useful, instructive and applicative, determined for rational solutions in this countries. It could be a contribution for affirmation of regional development in this part Europe, which is serious and inevitable duty (mission) that follows.
Keywords: 330; region; regionalization; Southeast Europe; euro-integrations